2011
DOI: 10.5007/1980-0037.2009v11n3p286
|View full text |Cite
|
Sign up to set email alerts
|

Circunferência da cintura, índice de massa corporal e fatores de risco cardiovascular na adolescência.

Abstract: Rev Bras Cineantropom Desempenho Hum 2009, 11(3):286-291Resumo -Embora diversos autores afirmem que a medida da circunferência da cintura (CC) é um indicador de fatores de risco cardiovascular mais confiável se comparado ao índice de massa corporal (IMC) e outros indicadores de adiposidade, estes resultados ainda não são conclusivos para população exclusivamente pediátrica. O Objetivo do presente estudo foi relacionar a CC e IMC com os fatores de risco para doenças cardiovasculares em adolescentes. A amostra f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
3
1
7
Order By: Relevance
“…Percentages of elevated BMI in this study are higher than results found in studies conducted in the South region of Brazil (Bozza et al, 2009;Terres, Pinheiro, Horta, Pinheiro & Horta, 2006). However, some similarities exist with the study by Suñe et al (2007), who found 27.8% of overweight and 21.6% obesity for the boys and girls from the State of Rio Grande do Sul, Brazil and with findings by Guedes, Guedes, Barbosa, Oliveira and Stanganelli (2006), who found overweight and obesity rates of 30.6% for girls and 26% for boys (7-18 years of age) from the North region of the State of Paraná, Brazil.…”
Section: Discussioncontrasting
confidence: 92%
“…Percentages of elevated BMI in this study are higher than results found in studies conducted in the South region of Brazil (Bozza et al, 2009;Terres, Pinheiro, Horta, Pinheiro & Horta, 2006). However, some similarities exist with the study by Suñe et al (2007), who found 27.8% of overweight and 21.6% obesity for the boys and girls from the State of Rio Grande do Sul, Brazil and with findings by Guedes, Guedes, Barbosa, Oliveira and Stanganelli (2006), who found overweight and obesity rates of 30.6% for girls and 26% for boys (7-18 years of age) from the North region of the State of Paraná, Brazil.…”
Section: Discussioncontrasting
confidence: 92%
“…In line with this and other studies 4,6,13 , the nutritional status classification occurs by means of BMI. For the general population, this is a fast, easy and inexpensive method; however, it does not describe the variation that occurs in the body composition of individuals, and admitting its inadequacy as a quantitative marker of body fat is a consensus 4,7 .…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, a study involving 354 students aged 17 to 19 years from the state of Bahia, pointed overweight and obesity of 4.0% among adolescents studied 22 . In another study in Curitiba, it was found that 17% of boys and 21% of girls have undesirable nutritional status 6,23 . Studies on overweight and obesity in children and adolescents use different classification criteria.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Em algumas regiões brasileiras, a prevalência de SO em crianças com idade inferior a 10 anos pode ultrapassar os 40% 4,5 , tornando o fato um problema de saúde pública 6 . O SO são transtornos multifatoriais e estão associados ao nível de atividade física 7 .…”
Section: Introductionunclassified